Pyloroantrectomy and Pedunculated Short Gastric-Tube Interposition in Esophageal Carcinoma Patients Associated With Early Gastric Adenocarcinoma - Sato, Yu; Kanda, Tatsuo; Kosugi, Shin-ichi; Ishikawa, Takashi; Tada, Tetsuya; Wakai, Toshifumi (International surgery, 2019)
Gastric carcinoma is one of the most common secondary malignancies in esophageal cancer patients. We herein report our surgical procedure for esophageal reconstruction in esophageal cancer patients associated with synchronous or metachronous early gastric adenocarcinoma. Gastric adenocarcinoma was removed by pyloroantrectomy with preservation of the right gastroepiploic artery and vein, and a pedunculated short gastric tube was used as an esophageal substitute in a Roux-en-Y fashion. Surgical data of 6 esophageal cancer patients who underwent this type of surgery between 1993 and 2012 were analyzed. Three patients had synchronous early gastric carcinoma and the remaining 3 patients had metachronous early gastric adenocarcinoma. The gastric tube was easily pulled up to the neck and no problems occurred during this procedure. Postoperative complications, including leakage of esophagogastrostomy, acute respiratory failure, and diffuse peritonitis, were observed in 3 patients. No patients suffered from necrosis of the gastric tube. Although 3 patients died of other diseases, gastric cancer recurrence has not been observed to date. Despite the need for precaution to ensure technical safety, pyloroantrectomy and esophageal reconstruction using a pedunculated short gastric-tube are oncologically feasible as a potential curative surgery for esophageal cancer patients with early gastric adenocarcinoma.